Drought stress and osmo-priming effects on physiological and biochemical characteristics of Ocimum basilicum - nassiry, Bahram Majd; Mohammadi, Neda (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Â Â Â One of the effects of reducing water content on soil is reduction of growth and development of seedlings and variation of field development. Seed priming technique has been known as a challenge to improve germination and seedling emergence under different environmental stresses. The objectives of this research were to evaluate the effects of osmo-priming on germination characteristics and changes of proline, protein and catalase activity of Ocimum basilicum seeds. Results showed that drought stress reduced the germination characteristics and drought stress in -8 bar was the critical stress.Â Priming treatments were include KNO3, PEG and NaCl by 0, -4 and -8 bar concentrations. The seeds were primed with those materials for 8 and 16 hours. The highest germination characteristics were obtained from nitrate potassium in -8 bar for 16 hours priming. Therefore the best seed treatment under drought stress during germination was obtained from the osmo-primed with -8 bar nitrate potassium for 16 hours. The drought stress increased proline and catalase activity but reduced total protein. Priming treatment increases proline, total protein and catalase activity under drought and control conditions. It is concluded that priming results in improvement in germination components of Ocimum basilicum in drought stress conditions and increases the resistance to drought stress with improvement of proline, protein and catalase activity in germination phase.